Cement Percent Effect on the Shear and Interface Strength of Remolded Cement Treated Sand - Rashied, Zahraa N. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2022)
This research aims to simulate the behavior of remolded cement treated poorly graded sand in term of shear and interface strength using the direct shear test. Different percentages of cement up to 15% by weight are added to the soil samples. Compacted cement treated soil samples are prepared at the optimum moisture content and left for 28 days in the humidity room then distributed to use them for the remolding samples preparation. The shear strength parameters for both cases soil to soil interface and concrete to soil interface are predicted, where the results show that the interface strength parameters are higher than the shear strength parameters of the remolded soil samples. The increase in cement percent increases the cohesion (C) of the treated soil, whereas the interface cohesion (Cint.) has a maximum value at 10% of added cement, and the maximum percent between cohesion (Cint.) and soil cohesion (C) is of 76.2% at 0% added cement. Moreover, the results show an increase in the interface angle of friction (δ) and a decrease in the angle of friction (φ) as the percent of cement increases. The maximum percent between interface angle (δ) and angle of friction (φ) is 63.5% at 15% of the added cement. The hardened cement in the remolded case adheres to sand grains and works as soil grains with different sizes that lead to changes in the shear properties of the soil.